Enhancing Fine Motor Skills Through a Task-Oriented Training-Based Collage Play Method for Hyperactive Children Aged 4–5 Years at TK Negeri 1 Teluk Pandan - Jumarni; Rendy Roos Handoyo (International Journal of Social Sciences and Humanities, 2026)
This study aimed to improve the fine motor learning process, which had previously been less effective due to the limitations of the teaching methods used, causing hyperactive children to have difficulty maintaining focus and actively participating in learning activities. The improvement in the learning process was indicated by increased attention, participation, and engagement during classroom activities. In addition, this study aimed to improve the fine motor skills of hyperactive children aged 4–5 years through a collage play method based on Task-Oriented Training (TOT) at TK Negeri 1 Teluk Pandan. This study employed Classroom Action Research (CAR) using the Kemmis and McTaggart model, which was conducted in two cycles consisting of planning, action, observation, and reflection stages. The implementation of the TOT-based collage method involved task orientation, demonstration, guided practice, independent practice, and feedback with reinforcement. The subjects of the study were two hyperactive children aged 4–5 years. Data were collected through observation, documentation, and field notes, while data analysis was conducted using descriptive quantitative and qualitative techniques. The findings showed that the TOT-based collage play method improved children's fine motor skills, as indicated by better eye-hand coordination, pinching ability, accuracy in attaching materials, and neatness of the final work. The fine motor skill percentage of subject GF increased from 45% in the pre-action stage to 60% in Cycle I and 90% in Cycle II, while subject AZ improved from 40% to 65% and reached 95% in Cycle II. Therefore, the collage play method based on Task-Oriented Training was effective in developing the fine motor skills of young hyperactive children.